Metabolic syndrome and symptom resolution in depression: a 5-Year follow-up of older adults - Virtanen, M; Ferrie, J; Akbaraly, T; Tabak, A; Jokela, M; Ebmeier, K; Singh-Manoux, A; Kivimäki, M (Physicians Postgraduate Press, 2017)
Objective: Although metabolic syndrome is associated with the incidence of depression, little is known about its contribution to the course of depression. We examined whether metabolic syndrome and its components are associated with long-term symptom resolution in older adults with depressive symptoms. Methods: Data from 965 participants in the Whitehall II cohort study (mean age = 62 years at baseline) were used to generate 1,172 person-observations of metabolic syndrome and its components (abdominal obesity, low level of high-density lipoprotein [HDL] cholesterol, high level of triglycerides, hypertension, and elevated fasting glucose or diabetes). All participants were depression cases at the beginning of 2 consecutive follow-up cycles: from 2002–2004 to 2007–2009 and from 2007–2009 to 2012–2013 (mean follow-up = 4.6 years). Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression scale caseness at the beginning and the end of the 2 cycles. Results: In multivariable adjusted analyses, metabolic syndrome per se was not associated with symptom resolution. Of its components, low HDL cholesterol (risk ratio [RR] = 0.82; 95% CI, 0.68–1.00; P = .045) and high triglyceride levels (RR = 0.81; 95% CI, 0.70–0.95; P = .007) were associated with a lower likelihood of symptom resolution. These findings were replicated in a subpopulation without coronary heart disease and stroke (RR = 0.77 [95% CI, 0.63–0.95; P = .015] for low HDL cholesterol; RR = 0.79 [95% CI, 0.67–0.94; P = .006] for high triglycerides). Conclusions: Low HDL cholesterol and high triglyceride levels are associated with lower likelihood of long-term symptom resolution in depression. These data suggest that an adverse lipid profile, but not other components of metabolic syndrome, may delay recovery from depression.